LABORATORY INVESTIGATION ON AN GIANG SOIL MIXED WITH DRY CEMENT (Malaysian Journal of Civil Engineering, 2018)
The soil-cement mixing technology is a technique mixing the in-situ soil with cement to create a new material, soil-cement or soilcrete, having better engineering properties than those of the in-situ soil such as higher strength and higher stiffness. This study investigates laboratory behaviors of local soil mixing with dry cement that will be used to construct rural road pavement for light weigh trucks (<= 2.5 tons) in An Giang province. More than 200 soil cement mixing samples were made with various cement contents at different water contents and cured at different durations. The results indicate that local fine sand with a cement content of 10% or higher can improve significantly the compression strength and secant modulus of the in-situ soil at least 15 and 50 times at 21 curing days, respectively. Therefore, a 0.5-m sand mixed with 10% to 12.5% cement can create a pavement that allows light trucks traveling safely.